Efektifitas Penerapan Aplikasi Sisnaker pada Dinas Tenaga Kerja dan Transmigrasi Provinsi Sumatra Barat - Muhammad Ananda Arif; Ika Lestari Zain; Rio Delfiro; Febi Febriyanti; Mutiara Monika Rizaldi; Syamsir Syamsir (Universitas Palangka Raya, 2022)
The purpose of this study is to find out the implementation of the Manpower Application at the West Sumatra Province Manpower Office. In this study, primary data will be obtained from the results of interviews with someone (informant). This research uses a qualitative method, namely a method that focuses on reasoning based on objective social reality. The type of research used is a qualitative research method using a descriptive approach. The application of this qualitative method aims to make it easier to understand multiple realities, presenting an essential relationship between writing and reality in the field. This method is more sensitive and adjusts to the form of the value encountered. In using this method it aims to find problems more openly, so the writer will interview Baznas informants in the city of Padang, in which case the writer interviewed BKOL staff, namely Mr. Ahmad Ridho. SH, Then administrative staff, namely Mrs. Yen. Data collection techniques using interviews, observation and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusions/verification. The Sisnaker information management system was introduced at the W Sumatra Disnaker in 2019. Through this Sisnaker it is expected to be able to provide accountable and transparent services and information to all its users. The existence of Sisnaker is a new breakthrough for the West Sumatra Manpower Office in providing all forms of services such as training, information on job vacancies, information on overseas internships, etc.